Legislative Discourses on Contemporary Slavery in Brazil: An analysis from the debates about the Constitutional Amendment Proposal nº 438/2001 - Resende Homem da Costa, Eduardo Antonio; Hora Góis, João Bosco (Americanía: Revista de Estudios Latinoamericanos, 2022)
This article aims to analyze the perceptions of parliamentarians about contemporary slave labour in Brazil. We examined the opposition speeches to the Constitutional Amendment Proposal (PEC) nº 438/2001, processed between 1999 and 2014. That proposal aimed to establish the expropriation of properties where such a form of work was found. From a methodological point of view, we use Critical Discourse Analysis. Several discursive strategies were identified in order to avoid the approval of the referred PEC. Among them, we chose to analyze the categories that we call ‘inversion of guilt’, ‘fantasy’, and ‘exceptionality’. The study of the speeches showed the inexistence of proposals of policies to confront the issue, policies that were pushed aside in the name of an evasive, conservative and even reactionary debate. We observed an evident concern of parliamentarians with agribusiness but a lesser concern in addressing the conditions in which the enslaved workers rescued by state inspection were found.